Cost‐effectiveness of caesarean sections in a post‐conflict environment: a case study of Bunia, Democratic Republic of the Congo. (11th June 2013) - Deboutte, Danielle; O'Dempsey, Tim; Mann, Gillian; Faragher, Brian
Abstract : This paper demonstrates the feasibility of health services research in an unstable environment during the transition from crisis to development and its importance for future planning. Effectiveness and the cost of caesarean sections (CSs) were investigated in Bunia, a town affected by conflict and insecurity, in the Democratic Republic of the Congo (DRC) in 2008. The CS rate was 9.7 per cent of expected deliveries. All CSs in the study sample were emergency procedures. A humanitarian non‐governmental organisation (NGO) hospital, offering free services, performed 75 per cent of all CSs. The estimated provider cost for CS in 2008 at this hospital was USD 103, 514 (that is, USD 144 per CS). With a cost of between USD 3.8 and 9.2 per year of health adjusted life expectancy (HALE) gained, CSs at the NGO hospital were very cost‐effective. The estimates give an indication of funding requirements to maintain adequate access to CS after the departure of the humanitarian organisation.